Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray terhadap Hasil Belajar Fisika Siswa Kelas 8 SMP Negeri 3 Lubuklinggau - Ovilia Putri Utami Gumay (SPEJ (Science and Physic Education Journal), 2017)
This study aims to determine whether there is an influence of Two Stay Two Stray learning model on physics learning outcomes of students of class 8 SMP Negeri 3 Lubuklinggau. This research type is experiment with design that used is pretest posttest control group design. The population in this study is the entire class 8 SMP Negeri 3 Lubuklinggau. The sample in this research is two classes taken at random, where class 8.2 as experiment class and class 8.1 as class. Technique of collecting data used is test. Collected data were analyzed using t test. Based on the results of analysis of pre test data with 95 percent confidence level obtained tcount 0.477 and ttable 2,000 because tcount less than ttable, then obtained the conclusion that the experimental class and ontrol class is homogeneous. While the results of posttest data analysis with 95 percent confidence level obtained tcount 1.2244 and ttable 2,000 because t count lees than ttable, then obtained the conclusion that there are differences in the results of physics learning between classes taught by Two Stay Two Stray learning model and class taught with lecture and question and answer method in class 8 SMP Negeri 3 Lubuklinggau. Keywords: Two Stay Two Stay, Learning Outcome Students